The Determinants of Financial Stability of Islamic Banks in ASEAN - Wasilatur Rohimah; Oktaviana, Ulfi Kartika (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Financial stability is one of the drivers of economic growth, while Islamic banking currently dominates in global economic competition compared to other Islamic finance industry. Therefore, it is necessary to investigate the aspects that can affect the financial stability of Islamic banks. The purpose of this study is to analyze how capital structure, profitability, efficiency, and technology affect the financial stability (Z-Score) of Islamic banks in the ASEAN region. The study employs a panel data regretion. It utilizes documentation techniques such as the financial reports of each bank and other publicly available data. Sample selection is done through purposive sampling, resulting in a sample of 19 Islamic banks in ASEAN. The research concludes that capital structure significantly and positively influences stability, while efficiency has no impact on stability, and the financial soundness of ASEAN's Islamic banks is significantly impacted negatively by technology and profitability. Based on the findings of this research, the Islamic banks are required to pay more attention to the management of funds obtained from profitability as well as fund management for technology needs so as not to affect the financial stability of Islamic banks in ASEAN.